2015
DOI: 10.1007/s11240-015-0910-4
|View full text |Cite
|
Sign up to set email alerts
|

Terpenoid and flavonoid spectrum of in vitro cultures of Glycyrrhiza glabra revealed high chemical heterogeneity: platform to understand biosynthesis

Abstract: Simultaneous qualitative and quantitative assessment of eight flavonoids and two terpenoids were performed in fourteen in vitro raised morphogenic cultures of Glycyrrhiza glabra. Our study revealed that the spectrum and production of ten compounds, under investigation, were higher in organized tissue than the undifferentiated mass, however, aerial portions of the in vitro raised plants (leaf and stem) were found to be devoid of therapeutically relevant triterpenoid, glycyrrhizin. A correlation was observed bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Similarly, n-hexadecanoic acid, which was exclusively found in the in vitro derived root tissue, is known to exhibit anti-inflammatory, anti-bacterial and anti-oxidant properties [47,48]. Consistent with our findings, Khan et al [3] reported the presence of important flavonoids and triterpenoids in the in vitro cultures of G. glabra.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, n-hexadecanoic acid, which was exclusively found in the in vitro derived root tissue, is known to exhibit anti-inflammatory, anti-bacterial and anti-oxidant properties [47,48]. Consistent with our findings, Khan et al [3] reported the presence of important flavonoids and triterpenoids in the in vitro cultures of G. glabra.…”
Section: Discussionsupporting
confidence: 91%
“…Finally, the dried plant extract generated from the equal weight (1 g) of the starting material was dissolved in methanol before subjecting to GC-MS analysis with an injection volume of 1 μl. The procedure for glycyrrhizin extraction from the in vitro-regenerated G. glabra plants was essentially similar to the earlier published reports (Gupta et al 2013 ; Khan et al 2016 ).…”
Section: Chemical Analysissupporting
confidence: 72%
“…Temporal and spatial analyses were performed using in vitro-regenerated plantlets, plants grown under glass house conditions and field-grown plants. For elicitation studies, in vitro plants, cultured in liquid MS medium (3% sucrose supplemented with 0.05 μM of NAA), as described earlier from our lab (Gupta et al 2013 ; Khan et al 2016 ), were used. Each set of treatment and control was employed in triplicates and harvested on defined time.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the compounds contained in this plant were glycerin, butin, quercetin, and glabridin. 62 These compounds thought to play a role in the inhibitory activity against Malassezia was glabridin. Previous studies had shown that glabiridine isolates trigger the overexpression of apoptosis-inducing factor genes in Candida albicans .…”
Section: Discussionmentioning
confidence: 99%